Pathogens for the Control of Weeds [and Discussion] - J. M. Cullen; S. Hasan; W. D. Hamilton; A. E. Akingbohungbe; J. W. Deacon (Philosophical transactions. Biological sciences, 1988)
The potential of pathogens for controlling plant populations has often been underestimated because of the subtle nature of their effects and the fact that only the final population equilibrium is observed. The potential exists for restoring such equilibria by classical biological control where they have become imbalanced, or for manipulating the host-pathogen system by the use of mycoherbicides, i.e. increasing the inoculum load. The use of exotic pathogens in classical control is often limited by considerations of sufficient host specificity for introduction into a new environment, whereas use of mycoherbicides is limited by the need to develop commercially viable systems of production, storage and application. Both approaches are subject to legislative restraints, classical control because of the inherent aim of establishing a new, freely dispersing organism throughout a region and mycoherbicides because they are subject to registration and patenting requirements. Neither the presence of a more variable genome in outbreeding plant species nor the high degree of specialization of obligate parasites are seen as significant restraints in re-establishing population equilibria in new environments. Sufficient effectiveness and safety have now been demonstrated in enough programmes to overcome initial hesitancy and considerable increase in activity in this field can be observed.